Loss of expression of the SWI/SNF chromatin remodeling subunit BRG1/SMARCA4 is frequently observed in intraductal papillary mucinous neoplasms (IPMNs) of the pancreas - Molin, Marco Dal (2011)
A better molecular characterization of Intraductal Papillary Mucinous Neoplasm (IPMN), the most frequent cystic precursor lesion of pancreatic adenocarcinoma, may have a pivotal role in its early detection and in the development of effective therapeutic strategies. BRG1, a central component of the chromatin remodeling complex SWI/SNF regulating transcription, is inactive in several malignancies. In this study we evaluate the Brg1 expression in IPMN in order to better understand its role in the pancreatic carcinogenesis. Tissue microarrays (TMAs) of 66 surgically resected IPMNs were immunolabeled for the Brg1 protein. Expression patterns were then correlated with clinicopathologic parameters. Normal pancreatic epithelium strongly immunolabeled for Brg1. Reduced Brg1 expression was observed in 32 (53.3%) of the 60 evaluable IPMN lesions and occurred more frequently in high-grade IPMNs (13 of 17 showed loss; 76%) compared to intermediate-grade (15 of 29 showed loss; 52%) and low-grade IPMNs (4 of 14 showed loss; 28%) (p=0.03). A complete loss of Brg1 expression was observed in 5 of the 60 (8.3%) lesions. Finally, a decrease in Brg1 protein expression was furthermore found in a low-passage non-invasive IPMN cell line by Western blot analysis. We did not observe correlation between Brg1 expression and IPMN subtype or with location of the cyst. We provide first evidence that Brg1 expression is lost in noninvasive cystic precursor lesions of pancreatic adenocarcinoma.